Effect of 7-Difluoromethyl-5, 4΄-dimethoxygenistein on aorta atherosclerosis in hyperlipidemia ApoE-/- mice induced by a cholesterol-rich diet - Zhang Y; Li L; You J; Cao J; Fu X (Dove Medical Press, 2013)
Yong Zhang,1,2 Lesai Li,3 Jiliang You,2 Jianguo Cao,2 Xiaohua Fu2 1Department of Hematology, Xiangya Hospital, Central South University, Changsha, People's Republic of China; 2College of Medicine, Hunan Normal University, Changsha, People's Republic of China; 3Department of Gynecologic Oncology, Tumor Hospital Xiangya School of Medicine of Central South University, Changsha, People's Republic of China Purpose: 7-Difluoromethyl-5, 4΄-dimethoxygenistein (DFMG), prepared by the difluoromethylation and alkylation of Genistein, is an active new chemical entity. Its anti-atherosclerosis effect was found in a series of studies in vitro. In this article, we explored and evaluated the anti-atherosclerosis effect via its protection of endothelial function in ApoE-/- mice that were fed a high-fat diet. Methods: Five C57BL/6J mice were selected as a control group and were fed a 1% high-fat diet (control group, n = 5). Five ApoE-/- mice that were fed a high-fat diet for 16 weeks were selected as the atherosclerosis model group (model group, n = 5). In the phase I study, 25 ApoE-/- mice were provided a prophylactic treatment with different drugs at the beginning of the 16 week high-fat diet: 5 mg/gk genistein (genistein 1 group, n = 5), 5 mg/kg lovastatin (lovastatin1 group, n = 5), 2.5 mg/kg DFMG (DFMG L1 group, n = 5), 5 mg/kg DFMG (DFMG M1 group, n = 5), and 10 mg/kg DFMG (DFMG H1 group, n = 5). In the phase II study, 25 atherosclerosis model, ApoE-/- mice were treated with different drugs and fed a high-fat diet for 16 weeks: 5 mg/gk genistein (genistein 2 group, n = 5), 5 mg/kg lovastatin (lovastatin 2 group, n = 5), 2.5 mg/kg DFMG (DFMG L2 group, n = 5), 5 mg/kg DFMG (DFMG M2 group, n = 5), and 10 mg/kg DFMG (DFMG H2 group, n = 5). The plasma levels of lipids, von Willebrand factor (vWF), and nitrite were compared between phases I and II. Endothelium-dependent relaxation (EDR), aortic lesion development, and quantification in thoracic aortas were measured during these two phase studies. Results: Compared to the model group, the lipid and vWF plasma levels were significantly lower, the plasma nitrite levels were significantly higher, the fatty streaks of aortic lesions were significantly lower, and the endothelium dependent relaxation was significantly higher after both phase studies (P < 0.05). The DFMG supplementation led to significant plasma nitrite increment in all groups after both phase studies (P < 0.05).There were significantly decreased fatty streaks of aortic lesions in DFMG-prevented and DFMG-treated mice (P < 0.05). There was a significant increase in EDR in all prophylactic treatment groups and treatment groups (P < 0.05). We further demonstrated that the preventative effect was more obvious than the therapeutic effect. Conclusion: Our results suggest that DFMG could work in prophylactic and therapeutic treatments for atherosclerosis development. Keywords: 7-Difluoromethyl-5, 4΄-dimethoxygenistein (DFMG), atherosclerosis, ApoE-/- mice, endothelium dysfunction, prevention